Every performance is a stage: musical stage theory as a novel account for the ontology of musical works - Moruzzi, Caterina (Wiley, 2018)
This paper defends Musical Stage Theory as a novel account of the ontology of musical works. Its main claim is that a musical work is a performance. The significance of this argument is twofold. First, it demonstrates the availability of an alternative, and ontologically tenable, view to well-established positions in the current debate on musical metaphysics. Second, it shows how the revisionary approach of Musical Stage Theory actually provides a better account of the ontological status of musical works.